Conceptual harmonization in forensic sciences: a terminological view from forensic clinic (2015)
Introduction: We highlight the terminological value of conceptual harmonizationin the medical-legal field, whose approach was applied in the area of forensic clinic based on the research results. We sought to determine a comprehensive conceptual system of technical-scientific terms in specific contexts of the forensic field. Methodology: Qualitative application in the context of tgt and terminology modeling, which allowed to track documents from the National Institute of Legal Medicine and Forensic Sciences, Medellin, with Cratilo software. The result of the analysis was subjected to evaluation by experts at Validation Workshops. Results: From the definition and analysis for conceptual precision, a total of 136 basic concepts were obtained, which constitute this conceptual system. Conclusions: The language in all areas of knowledge is transverse and accuracy always depends on context, facilitatinh fluent and reliable communication among the existing disciplines. By avoiding opacities in the everyday technical-scientific language for those involved in the judicial system, communication among experts and theirs with laymen and professionals in other fields of knowledge is optimized.